Environmental salinity and osmoregulatory processes in cultured flatfish. (17th March 2014) - Ruiz‐Jarabo, Ignacio; Herrera, Marcelino; Hachero‐Cruzado, Ismael; Vargas‐Chacoff, Luis; Mancera, Juan M; Arjona, Francisco J
Abstract: The aim of this study was to carry out a comparative analysis of the osmoregulatory properties and associated energy metabolism of euryhaline flatfish species that are cultured in the world. Culture of flatfish (pleuronectiformes) requires stage‐ and species‐dependent osmotic conditions for rearing. Additionally, geographic origin of broodstock animals is another factor to be taken into account for the culture of pleuronectiformes. Larval and juvenile stages of many flatfish species are cultured in large nurseries situated in estuaries and shallow marine habitats, where the environmental salinity is close to the iso‐osmotic point of their internal milieu . This fact implicates an advantage in terms of energy savings for osmoregulatory purposes. Thus, this 'saved' energy can be derived to other physiological processes, such as somatic growth. However, this scientific presumption does not always results in an optimal growth for many flatfish species. Indeed, iso‐osmotic culture conditions can evoke a higher allostatic load than that in the usual hyper‐osmotic environment where flatfish species live wildly. Optimization of flatfish culture thus requires adjustments of the osmotic culture conditions to the specific osmoregulatory and metabolic demands that eventually determine the allostatic load and consequently condition growth rates. In this sense, the geographical location of aquaculture farms and the osmoregulatory‐based selection of the species to be cultivated in a particular area become critical factors to be considered for optimal flatfish culture.